Analysis of Water Balance in Nyaen Irrigation Area Sukoharjo Regency - Muhammad Fitra Zidane; Erni Mulyandari; Kukuh Kurniawan Dwi Sungkono (Syntax Corporation Indonesia, 2024)
Nyaen Weir is one of the weirs in Sukoharjo Regency. This weir has an irrigation area called the Nyaen irrigation area. The Nyaen irrigation area experiences water shortages in the third planting period. Therefore, further analysis is needed to overcome the water shortage appropriately. This study aims to determine the water balance in the Nyaen Irrigation Area. The method used is direct observation along with a quantitative descriptive method. The analysis stage begins with a site survey to discover the problems in the irrigation network and then collect secondary data at the research location. The water balance analysis step is to compare the availability of water with irrigation water needs. According to the water balance analysis in the Nyaen Irrigation Area, it is not balanced because the right intake is 25% sufficient, and the left intake is 75% acceptable.